Impact of interdependence between supply chain partners on strategic alliance outcomes: role of relational capital as a mediating construct - Sambasivan, Murali; Loke, Siew Phaik; Mohamed, Zainal Abidin; Yee, Choy Leong (Emerald Group Publishing, 2011)
Purpose: The aims of this paper are: to argue the role of Kelley's personal relationship theory (PRT) in explaining the maintenance and success of alliance outcomes; to argue the inclusion of communication between supply chain partners as a major component of relationship capital in addition to trust and commitment; to test the impact of interdependence between supply chain partners on strategic alliance outcomes; and to test the role of relationship capital as a mediating construct between interdependence. Design/methodology/approach: A questionnaire was constructed and sent to 2,156 supply chain managers in Malaysia. The questionnaire captured three constructs: interdependence – task, goal and reward; relationship capital – trust, commitment, and communication; and strategic alliance outcomes – goal, value‐creation, and re‐evaluation. The companies were selected randomly from the Federation of Malaysian Manaufacturers (FMM) directory. Structural equation modeling (SEM) was used to test the hypotheses. Findings: The major findings are: communication must be included as a major component of relationship capital in addition to trust and commitment; Kelley's PRT plays a prominent role in explaining the maintenance and success of strategic alliance outcomes; interdependence has a significant relationship with relationship capital; relationship capital has a significant relationship with strategic alliance outcomes; and relationship capital acts as a pure mediator between interdependence and strategic alliance outcomes. Originality/value: This research contributes significantly to the theoretical and empirical developments that enrich the strategic alliance literature.